Baltų šaknis *dr̥-ž- - Karaliūnas, Simas (Baltistica, 1971)
THE BALTIC ROOT *dr̥-ž-An attempt is made here to give a satisfactory explanation of the provenance of various allomorphs based on the Common Baltic root *dr̥ -ž-> *dirž- attested in Lith. diržti “to flay, skin”, dir̃žas “belt, girdle; sash”, Latv. dir̂ža “belt, girdle; strap, thong”, Lith. déržti “hurry, make haste”, dar̃žas, Latv. dā̀rzs “kitchen-garden, flower garden”. The root *dr̥-ž- seems to be a Baltic innovation: it might contain a primitive root *dr̥- attested in Lith. dir̃ti “skin, strip off, bark, tear”, Latv. dirât “flay, skin” (cf. their cognates OCS derą, Goth. dis-taíran, Gr. δέρω, OInd. dr̥nā́ti, Arm. ter̆em, Toch. AB tsär-), enlarged with a suffix -ž-.A seṭ-variant *der-H- seems to have existed as well, cf. Lith. dìrti, OInd. dīrṇa-. Therefore it would not be unreasonable to assume that in proto-Baltic dialects there existed a full grade variant *dr-eH- as well as *d(e)r-H- and that the former functioned in a preterite system and the latter most likely belonged to a present system. Due to the analogy of *der-ž- / *dr̥-ž- they could have been enlarged with a suffix -ž-. After the syllabic laryngeal had been vocalized, i.e. *d(e)r-H-ž- → *dr-H̥-ž- → *draž-, a “heteroclitic” paradigm praes. *draž- (< *drH̥-ž-) : praet. *drēž- (< *dreH₁-ž-) was created in the proto-Baltic dialects. This kind of paradigm must have been a deviation, for forms within a paradigm could likely have differed in regard to their root vocalism quantitatively, but vot qualitatively. Due to the tendency for the root vocalism to become the same in all forms, two new paradigms could have been formed on the basis of the old one, namely praes. *drež- : praet. *drēž- and praes. *draž- : praet. *drāž-. That means that having fitted into the model praes. TVRT- : praet. TvRT- (cf. gẽria : gė́rė, kãria : kórė etc.) a present form with a normal root vocalism could have been created beside the existing preterite form *drēž- and respectively a preterite *drāž- with a long root vocalism might have been formed beside the existing present *draž-. We find the first paradigm attested in Lith. drė́žti “wear, tear, rend, scratch” and Latv. drêzt (: drēzt uguni “make up the fire”). The second paradigm is represented in Lith. dróžti, Latv. drāzt “plane, shave; cut out; point, sharpen; carve; hurry, make haste; strike, whip etc.”.Having followed the model T(R)ēTv- → T(R)ōTn-, the nouns with a root vocalism ō (> Lith., Latv. uo) seem to have been generated on the basis of praet. *drēž-: Lith. drúožas “stripe; region, zone”, druožė̃ “stripe”, druožlė̃ “shaving”, Latv. druõztala “shaving, small piece, bit”, from which afterwards such verbs as Lith. druõžti, driúožti “to wear, tear”, Latv. druoztalât “to cut a little and frequently” could have been derived. After the above model had ceased to operate nouns could have been produced without any vowel alternation: drêzt2→drȩ̄za “scolding; wigging”, drȩ̄zns “moist, damp”, drȩ̃gzna “cold and damp weather”; dróžti, drāzt → drožlỹs “plane”, drãzlis “shaving, chip, sliver”, drožnùs “which is easily to plane”, drāzns “naughty, frisk”, drožlė̃ “shaving”, dràza2 “crowd, throng; scab” etc.The allomorphs *driž- and *drīž- seem to be of late origin in both Lithuanian and Latvian. As a pattern for their formation the structural ratio TeR-T- : TiR-T- = TRe-T- : x, where x equates to TRi-T- / TRī-T-, can be suggested. In this way on the basis of the verb drė́žti, drêzt2 all forms with a vocalism in reduced grade could rather easily have been brought about: thus praet. *drēž → Lith. drýžti “to carry”, drỹžti “tear”, drýžas “streaky, striped, in streaks”, Latv. drīzȩna, drīzna “beam, ray”, and praes. *drež- → Lith. drìžti “take pains, weaken; feel shy”, drižė́ti “be afraid, feel shy, be diffident”, Latv. driz-nêt „grow stiff”.The full grade forms dríežti „tear“, dreĩžti “linger; tarry; be slow”, dríežas “lizard“ (cf. drýžas “lizard“ and drýžas “striped; stripy; motley”) and others are used only in Lithuanian. Thus being apparently late innovations they might have followed the productive pattern TRī-T- : TRie-T- resp. TRī-T- : TRēi-T-.In a similar way, i.e. by the ratio TaR-T- : TuR-T- = TRa-T- : x (x = TRu-T- / TRū-T-), the origin of the allomorphs *druž- / *drūž- can be accounted for. The basis for their formation could have been the forms of the verb Lith. dróžti, Latv. drāzt : praes. *draž- → Lith. drùžti “weaken, grow weaker”, drùžas “flogging, thrashing”, Latv. druzas “mud, mire, dirt” etc.; praet. *drāž- → Lith. Drūžė̃ “stripe” etc., Latv. drũzêt “be chilly; shiver with cold”, drūze “crowd, press, throng” etc. On the basis of this zero grade allomorphs, forms with an a-vocalism might have been generated in Latvian, cf. drauzs “brittle; rough, rude, coarse, harsh”, drauzs “Schinn, Schelfer”, drauza “mud, mire; waste, rubbish, offal (from a bark)” etc.